(3GdGJLGg GdeYGUQ dejRI JfGaSjI eSJOGeI s - (3aOhi (B, (3YHhs ((3GdLRGFQ(B:s (3OGQ EjdjGA ddfTQ hGdJhRjY(B,s, 2024)
(3jTjQ eUWdM PcGA GdCYeGd Edi GSJNOGe GdHjGfGJ hGdeYdheGJ dJMSjf YedjGJ GJNGP GdbQGQ aj GdeDSSGJ(B. (3hjTed Pdc LeY GdHjGfGJ ef eUGOQ eNJdaI, hJMdjdgG, hJbOjegG HWQjbI eagheI hSgdI GdGSJNOGe eG GdejRI GdJfGaSjI GdeSJOGeI agj GdbOQI Ydi JMbjb COGA eJahb Ydi GdefGaSjf Ydi GdeOi GdWhjd(B. (3hdcj Jchf GdejRI eSJOGeI, jLH Cf Jchf UYHI GdJbdjO ef bHd GdefGaSjf(B.(3dYdGbI Hjf PcGA GdCYeGd hGdejRI GdJfGaSjI GdeSJOGeI jdYH PcGA GdCYeGd OhQkG gGekG aj JMbjb GdejRI GdJfGaSjI GdeSJOGeI(B. (3agh jSGYO GdeDSSGJ Ydi(B: (3age YedGFgG HTcd CaVd(B: (3ef NdGd JMdjd HjGfGJ GdYedGA, jecf ddeDSSGJ age GMJjGLGJge hJhbYGJge HTcd CaVd, hJbOje efJLGJ hNOeGJ JdHj gPg GdGMJjGLGJ hGdJhbYGJ(B. (3JMSjf YedjGJgG(B: (3ef NdGd JMdjd GdHjGfGJ GdeJYdbI HYedjGJ GdeDSSI, jecf JMOjO fbGW GdVYa hGdYed Ydi JMSjfgG, eeG jDOj Edi RjGOI GdcaGAI hNaV GdJcGdja(B. (3GcJTGa aQU LOjOI(B: (3ef NdGd JMdjd GdHjGfGJ GdeJYdbI HGdShb hGdefGaSjf, jecf ddeDSSGJ GcJTGa aQU LOjOI ddfeh hGdJhSY(B. (3GJNGP bQGQGJ CaVd(B: (3ef NdGd JhajQ eYdheGJ ObjbI hehKhbI, jSGYO PcGA GdCYeGd GdeOjQjf Ydi GJNGP bQGQGJ CaVd hCcKQ GSJfGQI(B.s
(3eQGLY U(B.176-199s
Keywords: (3GdEOGQIs; (3GdefGaSIs; (3fXe GdeYdheGJ GdEOGQjIs